Identifying the Leadership Effectiveness of the Executive Leaders in Indonesia - Nurhayati, Dita Siti; Diliani, Anastasia (UI Scholars Hub, 2017)
This study introduces Public Leader Organization Scale (POLS) as the tool to identify the effectiveness of leadership in a public organization. To show the reliability and validity of this tool, a case study of subjective evaluation is addressed to three former and one active government leaders. The implication of the study is twofold: first that it shows POLS as an appropriate tool to be used in identifying public leaders' performance. This study finds that leader's consistency, listening communication skills, managing resources skill and exchange tactics become the strongest behaviors associated to government performance. Second, among these behaviors, leaders' personal integrity (consistency) is considered to contribute more to the region's performance rather than the leader's skills or the leader's influence. In essence, we believe that the current study findings will enrich the existing theory of leadership particularly in public organization issues.